PEMBUDAYAAN KARAKTER DISIPLIN TEPAT WAKTU DALAM EKSTRAKULIKULER DRUMBAND DI SEKOLAH DASAR - Aprilia Wulandari; Sutama (Universitas Negeri Medan, 2026)
Abstract: The purpose of this study is to describe and explore the cultivation of punctuality in extracurricular drum band activities in elementary schools, including arriving on time and leaving on time. This is a qualitative-ethnographic study. The research subjects consisted of the principal, supervising teacher, coach, and students participating in the drum band at the elementary school where the research was conducted. Data were collected through interviews, observations, and documents. Validation was conducted using triangulation of sources and methods. Data were analyzed inductively. The results of the study show that the cultivation of time discipline in the drum band is formed through planned training, the example set by the advisor, routine evaluations, and collaboration between the school and parents. Keyword: drum band, extracurricular activities, cultural activities, punctuality Abstrak: Tujuan penelitian ini adalah menguraikan dan mengeksplorasi pembudayaan karakter disiplin tepat waktu dalam kegiatan ekstrakulikuler drumband di sekolah dasar, meliputi hadir tepat waktu dan pulang tepat waktu. Jenis penelitian kualitatif-etnografi. Subjek penelitian terdiri dari kepala sekolah, guru Pembina, pelatih, dan siswa peserta drumband si SD tempat penelitian. Data dikumpulkan dengan wawancara, observasi, dan dokumen. Validasi dengan triangulasi sumber dan metode. Data dianalisis dengan induktif. Hasil penelitian menunjukan bahwa pembudayaan disiplin waktu drumband terbentuk melalui latihan terencana, keteladanan Pembina, evaluasi rutin, dan kolaborasi sekolah dan orang tua. Kata Kunci: drumband, kegiatan ekstrakulikuler, pembudayaan, taat waktu